ANALISA KINERJA KEUANGAN DITINJAU DARI RASIO LIKUIDITAS, PROFITABILITAS DAN AKTIVITAS PT. INDO POWER ENGINEERING DI SAMARINDA PERIODE 2016-2017 - Nahrowi, Enisa Faramitha (EKONOMIA, 2019)
This research was conducted at PT. Indo Power Engineering in Samarinda. Data collection techniques are library research (library research) that is data collection to obtain secondary data by collecting documents in the form of financial statements (income statement, balance sheet) and scientific work (journal). Formulation of the problem of whether liquidity ratios (current ratio, cash ratio), profitability ratios (gross profit margins, net profit margins, return on assets, return on equity) and activity ratios (receivable turnover, working capital turnover, fixed asset turnover, total asset turnover ) in samarinda in the financial statements of PT. Indo Power Engineering in 2016 compared to 2017 has decreased. The basic theory used in this study is financial management. While the analysis tool uses financial statements in the form of balance sheets and profit and loss. In addition to using liquidity ratios (current ratio, cash ratio), profitability ratios (gross profit margins, net profit margins, return on assets, return on equity) and activity ratios (receivable turnover, working capital turnover, fixed asset turnover, total asset turnover). From the calculation of the Liquidity Ratio in terms of the current ratio has decreased by 15.63%, Cash ratio has decreased by 10.88%. Profitability Ratio in terms of gross profit margin decreased by 0.20%, Net profit margin decreased by 0.60%, ROA decreased by 3.17%, ROE decreased by 0.41%. Activity ratios in terms of receivable turnover decreased by 0.1 times, Working capital turnover did not experience a decrease or increase, the calculation results from 2016 and 2017 remain, Fixed asset turnover did not experience a decrease or increase, the calculation results from 2016 and 2017 fixed and total asset turnover decreased by 0.05%. The hypotheses (1,2,3,4,5,6,7 and 10) are accepted and the hypothesis (8, 9) is rejected. Performance in this company is good, it's just that from 2016 to 2017 has decreased.